X-ray line-broadening study on sputtered InGaN semiconductor with evaluation of Williamson-Hall and size-strain plot methods - Erdoğan, Erman (INDIAN ASSOC CULTIVATION SCIENCE, 2019)
The epitaxial growth of indium gallium nitride (InGaN) is stressed by the difference in the thermal expansion constant between the film and the substrates. This creates permanent stresses at high rates, such as preventing successful growth. The position expansion of in-plane and out-of-plane reflections with grazing incidence X-ray diffractometer was investigated using semi-experimental methods. The Williamson-Hall analysis and size-strain plot method were used to study residual stress and the isotropic and anisotropic behavior of InGaN epitaxial layer at different nitrogen gas flow rates. According to the results, harmony between the models was investigated. According to the results obtained, the sample with large crystal size, low stress value, and low energy density was proposed as ideal epitaxial growth.
Keywords: GIXRD; Williamson-Hall; SSP model; Indium gallium nitride; Sputtering; 71; 15; Ap; 71; 20; Nr; 71; 23; An; 71; 55; Eq